Intercropping Induces Changes in Specific Secondary Metabolite Concentration in Ethiopian Kale (Brassica carinata) and African Nightshade (Solanum scabrum) under Controlled Conditions - Ngwene, Benard; Neugart, Susanne; Baldermann, Susanne; Ravi, Beena; Schreiner, Monika (Frontiers in Plant Science, 2017)
Intercropping is widespread in small-holder farming systems in tropical regions and is also practiced in the cultivation of indigenous vegetables, to alleviate the multiple burdens of malnutrition. Due to interspecific competition and/or complementation between intercrops, intercropping may lead to changes in plants accumulation of minerals and secondary metabolites and hence, alter nutritional quality for consumers. Intercropping aims to intensify land productivity, while ensuring that nutritional quality is not compromised. This study aimed to investigate changes in minerals and secondary plant metabolites in intercropped Brassica carinata and Solanum scabrum, two important African indigenous vegetables, and evaluated the suitability of this combination for dryer areas. B. carinata and S. scabrum were grown for 6 weeks under controlled conditions in a greenhouse trial. Large rootboxes (8000 cm3 volume) were specifically designed for this experiment. Each rootbox was planted with two plants, either of the same plant species (mono) or one of each plant species (mixed). A quartz sand/soil substrate was used and fertilized adequately for optimal plant growth. During the last 4 weeks of the experiment, the plants were either supplied with optimal (65% WHC) or low (30% WHC) irrigation, to test the effect of a late-season drought. Intercropping increased total glucosinolate content in B. carinata, while maintaining biomass production and the contents of other health related minerals in both B. carinata and S. scabrum. Moreover, low irrigation led to an increase in carotene accumulation in both mono and intercropped S. scabrum, but not in B. carinata, while the majority of kaempferol glycosides and hydroxycinnamic acid derivatives of both species were decreased by intercropping and drought treatment. This study indicates that some health-related phytochemicals can be modified by intercropping or late-season drought, but field validation of these results is necessary before definite recommendation can be made to stakeholders.